Floating debris dynamics in a tidal strait: transport and retention in Sundklakkstraumen, Lofoten - Peygham Ghaffari; Håvard Espenes; Eli Børve; Stine Hermansen; Øyvind Leikvin; Johanne Rydsaa; Rui Pires; Vilde Sørnes Solbakken; Marthe Larsen Haarr (Frontiers in Marine Science)
Understanding the transport and retention of floating plastic debris in fjords and coastal systems is essential for targeted mitigation strategies. This study investigates surface transport dynamics in Storvika and Sundklakkstraumen, a tidally energetic system in the Lofoten archipelago, Northern Norway. We combine GPS-tracked drifter observations with high-resolution 2D and 3D hydrodynamic modeling to assess how tidal forcing shapes transport pathways, convergence zones, and debris retention. Field deployments during spring and neap tides revealed strong contrasts in particle behavior, with spring tides promoting rapid flushing along energetic channels and neap tides supporting localized recirculation and short-term retention. The 3D model outperformed the 2D configuration in resolving sub-basin features, achieving skill scores of ss = 0.833 compared to 0.804, and reproducing trajectory structures with endpoint errors under 100 meters. Retention zones increased significantly during weaker tidal forcing relative to strong tidal forcing, with a 40% increase in attracting Lagrangian Coherent Structures and a 50% rise in domain-wide flush-out time. Residence time, revisit probability, and flow structure metrics consistently indicated higher retention during neap tide. Spatial diagnostics identified three possible accumulation hotspots, primarily active under neap conditions, accounting for over 40% of total residence time while occupying only ∼ 20% of the basin area. Low kinetic energy, reduced transport efficiency, and strongly attracting FTLE structures characterized these zones. The combined modeling–observation approach highlights the dominant role of the tidal phase in modulating short-term transport versus the temporary entrapment of debris. While the model excludes wind, waves, and high-frequency runoff events, the sheltered nature of the domain and minimal river influence limit their significance in this setting. This validated multi-diagnostic approach provides a transferable methodology for assessing retention in similarly complex coastal environments, supporting pollution mitigation, aquaculture planning, and operational forecasting efforts.